Inter UAV communication using zigbee for formation control - Liu, Yuhui (2017)
Formation flying of Unmanned Aerial Vehicles (UAVs) has become a topic in rapid development due to the high-performance UAVs and its many potential advantages. Formation control supports collaborative movements. It allows wider sensing coverage which leads to improved surveillance capability and enhanced situational awareness for a UAV fleet. Formation control requires UAVs to fly based on both information from itself and other UAVs. The most common centralized leader-follower formation control may suffer significantly if the leading UAV is accidentally broken down or losses connection during a mission. When such situation happens, the whole fleet is likely to be paralyzed since the rest lacks information from the leader to carry on the mission. A more robust decentralized formation control is expected to overcome this issue. Such control requires support from an effective decentralized inter-UAV communication. Communication device ZigBee allows a long-distance transmission and suitable data rate to support the UAVs’ inter communication. Its ability of multiple hop transmission and Mesh networking allows a possibility of large-scale decentralized communication of UAV fleet. Therefore, ZigBee has a great potential for developing effective decentralized formation control. This project developed a ZigBee inter-UAV communication scheme with decentralized mesh network. A formation control simulation is conducted to test this scheme and the result demonstrated a reliable communication for formation control.